1987
DOI: 10.1136/bmj.294.6581.1185
|View full text |Cite
|
Sign up to set email alerts
|

Atopic manifestations in the acquired immune deficiency syndrome: response to recombinant interferon gamma.

Abstract: Six patients with the acquired immune deficiency syndrome (AIDS) had exacerbations or recurrences ofpreviously quiescent atopic disease when they developed immunodeficiency. Four developed a different atopic illness from that suffered previously. Atopic symptoms developed within three months after the patients developed AIDS or during prodromal illness. Two ofthe patients were treated with recombinant interferon gamma: both showed a string improvement in symptoms and cellular immunity.These results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Of note, AIDS is also characterized by a high incidence of drug reactions and other clinical manifestations that resemble IgE-mediated hypersensitivity reactions (25)(26)(27). Elevated levels of IgE have been reported in patients with AIDS, either with or without a previous history of atopy (27).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, AIDS is also characterized by a high incidence of drug reactions and other clinical manifestations that resemble IgE-mediated hypersensitivity reactions (25)(26)(27). Elevated levels of IgE have been reported in patients with AIDS, either with or without a previous history of atopy (27).…”
Section: Resultsmentioning
confidence: 99%
“…[17,27] In infants, the disorder may take the form of severe erythema and scaling of the face, scalp, and diaper area, sometimes progressing to erythroderma. [28,36] Atopic dermatitis: Parkin et al [53] documented the association of atopic manifestations with established AIDS. Atopic dermatitis appears to be triggered by HIV sero-conversion in genetically predisposed individuals.…”
Section: Inflammatory Dermatoses Pruritic Papular Eruption (Ppe): Ppementioning
confidence: 98%
“…Recent studies have indicated that helper factors released by activated T lymphocytes play a major role in the regulation of IgE secretion [19], 1L-4 is a T-cell-derived lymphokine that strikingly enhances the secretion of IgG 1 and IgE and stimulates mast cell growth. Moreover, it has been suggested that the induction of Fc(;Ri /CD23 on B cells seems to be specific for 1L-4 [16]. Recent work from several laboratories has shown that murine helper/inducer T-cell clones are composed of at least two nonoverlapping subsets that can be distinguished on the basis of their patterns of lymphokine secretion [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our re sults suggest that reduced IFNy generation may con tribute to defective NK cell activity in AD. Interest ingly, patients with AD treated with recombinant IFNy showed a striking improvement in symptoms and cellular immunity [16]. Generation of IFNy was analyzed in vitro because serum IFNy concentration in controls is normally below detectable levels.…”
Section: Discussionmentioning
confidence: 99%